Barriers to Physical Activity Participation Among Housewives: A Pilot Study - Pooja, Ramaniklal; Thirumalaya, Balaraman (2018)
Worldwide, more than 3 million preventable deaths in 2018 were attributed to physical inactivity rendering it the fourth most common cause of chronic disorders. In Malaysia, surveys found that women are less physically active than men. Although there is much research done focusing on women, limited research has been done from a perspective of a housewife in Malaysia. The objective of this study was to identify the prevalence, barriers and enablers of physical activity among housewives in selected states of Malaysia. A cross-sectional survey was undertaken whereby the participants were recruited through non-probability convenience sampling in Penang and in Selangor. A total of 62 responses was collected and GPAQ was used to identify the prevalence of physical activity. A self-developed questionnaire was used to assess the barriers and enablers. It was found that 41 (66.13%) housewives were having physical activity level lower than recommended levels. Top 3 barriers which were reported by the housewives were, no facilities in the neighbourhood, high cost of gym and no energy for physical activity after house chores. The majority of the respondents also showed a positive attitude in the willingness to attend campaign or talk or workshop about healthy lifestyle and physical activity in the future. The level of physical activity among housewives in Malaysia is low. Most of the housewives were presented numerous barriers that hinder them from participating in activity. Further studies in other are required.